2020
DOI: 10.12707/riv19081
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do debriefing estruturado como estratégia pedagógica em enfermagem de saúde familiar

Abstract: Background: The impact of simulation with structured debriefing as a pedagogical strategy in nursing education is unquestionable today. However, no references were found regarding the use of this strategy in family health nursing education. Objective: To evaluate structured debriefing associated with simulation as a pedagogical strategy in family nursing consultations. Methodology: A quantitative cross-sectional descriptive study was conducted with a sample of 169 students attending the 2 nd year of the Bachel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This scoping review was conducted to map the pedagogical methodologies used in family health nursing education. Two studies were included: one was conducted in Portugal by Silva et al (2020) and the other in Canada by Charron (2007).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This scoping review was conducted to map the pedagogical methodologies used in family health nursing education. Two studies were included: one was conducted in Portugal by Silva et al (2020) and the other in Canada by Charron (2007).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Several authors identified nurses' difficulty in developing clinical practices focused on the family as a unit of care (Figueiredo, 2013;Santos, 2012;Silva, 2016;Silva, 2013). However, this difficulty is not always attributed to the pedagogical methodologies used in training (Silva, 2016;Silva et al, 2020).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations